Analysis of the effect of DEK overexpression on the survival and proliferation of bone marrow stromal cells - Cakar, Turkan; Kandilci, Ayten (Walter De Gruyter Gmbh, 2019)
Objective: DEK is ubiquitously expressed and encodes a nuclear protein, which is also released from some cells. Overexpression of DEK suppresses proliferation of some blood cell progenitors whereas it increases proliferation of epithelial tumors. We showed that DEK is overexpressed in BM cells of 12% of multiple myeloma (MM) patients. Here, we aimed to test if DEK overexpression effects the proliferation and viability of BM stromal cells or MM cells co-cultured with DEK-overexpressing stromal cells, mimicking the BM microenvironment. Methods: DEK is stably overexpressed in the BM stromal cell line HS27A. Periodic growth curve and fluorescent activated cell sorting (FACS) analysis was performed to determine the effect of DEK overexpression on HS27A cells and MM cell lines (RPMI-8226 and U266) that are co-cultured with these HS27A cells. Results: We showed that, on the contrary to blood progenitors or ephitelial cells, DEK overexpression doesn't alter the viability or proliferation of the HS27A cells, or the MM cell lines which are co-cultured with DEK-overexpressing HS27A cells. Conclusions: Our results suggest that effect of DEK overexpression on the proliferation is cell type and context dependent and increased DEK expression is tolerable by the stromal cells and the co-cultured MM cell lines without effecting proliferation and viability.
Keywords: DEK; Stromal cells; HS27A cells; RPMI-8226 cells; U266 cells; Multiple myeloma